METODE PENDIDIKAN MENURUT PETUNJUK AL-SUNNAH - Nafiul Lubab (Kopertais Wilayah X Jawa Tengah, 2014)
AbstractEducation is very vital role in human life. The system of education in whicheducational methods is under constant continuous